МОГУЋНОСТИ ИМПЛЕМЕНТАЦИЈЕ ЕКОЛОШКИХ ПОРЕЗА У ЗЕМЉАМА У ТРАНЗИЦИЈИ - Костић, Стојан; Зекић, Владислав; Родић, Весна (Economics of Agriculture, 2011)
Environmental taxes, along with penalty system, represent one of the most important and most frequently used instrument in environmental policy management. Assumptions of their successful implementation in transitional countries are: institutional basis, simplicity, transparency, monitoring and control etc. Many obstacles stand in the way of their effective implementation in transitional countries, such as: reducing the competitiveness of a business entity, public resistance etc. Serbia has legal framework for the implementation of existing economic instruments, however, the main problem remains the unsatisfactory level of their application, and the fact that they serve almost exclusively for achieving fscal goals with a lack of incentives for reducion of environmental pollution.